LysGR1, a novel thermostable endolysin from Geobacillus stearothermophilus bacteriophage GR1 - Choi, Dahee; Kong, Minsuk (Frontiers in Microbiology, 2023)
Geobacillus stearothermophilus is a highly thermophilic, spore-forming Gram-positive bacterium that causes flat sour spoilage in low-acid canned foods. To address this problem, we isolated G. stearothermophilus-infecting phage GR1 from the soil and characterized its endolysin LysGR1. Phage GR1 belongs to the Siphoviridae family and possesses a genome of 79,387 DNA bps with 108 putative open reading frames. GR1 demonstrated a very low degree of homology to previously reported phages, indicating that it is novel. The endolysin of GR1 (LysGR1) contains an N-terminal amidase domain as an enzymatic active domain (EAD) and two C-terminal LysM domains as a cell wall binding domain (CBD). Although GR1 is specific to certain strains of G. stearothermophilus, LysGR1 showed a much broader lytic range, killing all the tested strains of G. stearothermophilus and several foodborne pathogens, such as Clostridium perfringens, Listeria monocytogenes, and E. coli O157:H7. LysGR1_EAD, alone, also exhibits lytic activity against a wide range of bacteria, including Bacillus cereus, which is not terminated by a full-length endolysin. Both LysGR1 and its EAD effectively remove the G. stearothermophilus biofilms and are highly thermostable, retaining about 70% of their lytic activity after a 15-minute incubation at 70 ℃. Considering the high thermal stability, broad lytic activity, and biofilm reduction efficacy of LysGR1 and its EAD, we hypothesize that these enzymes could act as promising biocontrol agents against G. stearothermophilus and as foodborne pathogens.